2003
DOI: 10.1016/s0016-7037(03)00081-4
|View full text |Cite
|
Sign up to set email alerts
|

Mercury transformations and exchanges in a high turbidity estuary:

Abstract: The speciation and partition of mercury in a macrotidal estuary (Seine estuary, France) was studied in order to explore the role of the high turbidity zone (HTZ) in mercury transfer to the adjacent coastal waters. Water and particles were analyzed to determine the concentrations of various mercury species, including monomethylmercury and the inorganic fraction. The exchangeable particulate mercury, which varies with salinity, and the mercury fraction associated with the amorphous oxyhydroxides were evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 41 publications
3
51
3
1
Order By: Relevance
“…dissolved Hg could not be explained by a conservative mixing of two end-members: terrestrial/allochthonous and non-terrestrial/ urban/atmospheric sources of Hg. Similar non-conservative patterns of Hg changes from freshwater to estuary had also been previously reported (Han et al, 2006;Can ario et al, 2008;Laurier et al, 2003;Balcom et al, 2008). Notably, in high salinity water, inorganic ligands (e.g.…”
Section: Decoupling Between Spatial Distributions Of Dom and Hgsupporting
confidence: 86%
See 2 more Smart Citations
“…dissolved Hg could not be explained by a conservative mixing of two end-members: terrestrial/allochthonous and non-terrestrial/ urban/atmospheric sources of Hg. Similar non-conservative patterns of Hg changes from freshwater to estuary had also been previously reported (Han et al, 2006;Can ario et al, 2008;Laurier et al, 2003;Balcom et al, 2008). Notably, in high salinity water, inorganic ligands (e.g.…”
Section: Decoupling Between Spatial Distributions Of Dom and Hgsupporting
confidence: 86%
“…As shown in Table S2 Conaway et al, 2003;Choe et al, 2004). Yet our values were still higher than some other estuaries (e.g., New York/ New Jersey harbor estuary of US; Balcom et al, 2008;and Seine estuary of France;Laurier et al, 2003). Additionally, the Xiaoqing River showed a higher concentrations of dissolved Hg than the tributaries of the Chesapeake Bay, US (Lawson et al, 2001).…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…Iron can also affect Hg mobility in sediment. For example, the dissolution of Fe(III) oxides has been observed to increase the pore-water concentration of Hg (Gobeil and Cossa 1993;Gagnon et al 1996;Laurier et al 2003), which in turn could increase Hg bioavailability to methylating bacteria. This could be another explanation for the observed relationship in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…have been reported (e.g., Hedges and Keil, 1995;Thomsen et al, 2001;Laurier et al, 2003;Treignier et al, 2006), there have been only a few geochemical studies of older turbiditic sedimentary sequences for reconstruction of long time-scale paleoenvironments and material-cycling systems. Hoefs et al (2002) reported the organic geochemical investigations of Miocene to Pleistocene turbiditic sequences collected by Ocean Drilling Program (ODP) Leg 157 on the Madeira Abyssal Plain (MAP) off northern Africa, which showed variations in biomarker compositions that were attributed to redox conditions (oxygen exposure time) of the depositional environment.…”
mentioning
confidence: 99%